2023
DOI: 10.3389/fpsyg.2023.1127477
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Psychotic experiences, social cognition and pragmatic communication in the psychosis continuum

Abstract: Editorial on the Research Topic Psychotic experiences, social cognition and pragmatic communication in the psychosis continuum The Research TopicThe RT is composed of 11 articles covering original research to reviews, conceptual analysis, and theoretical and perspectives articles from 74 researchers working in 12 different countries. More in detail, the main themes that emerged and were addressed are: 1) Psychosocial and cognitive factors that determine the development or persistence of psychotic experience in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Over the years, it has been shown that the capacity to mentalize plays an important role in mental health [2,24,25]. For example, it is thought to be a crucial factor in the relational difficulties and interpersonal stress characteristic of schizophrenia and antisocial and borderline personality disorders [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, it has been shown that the capacity to mentalize plays an important role in mental health [2,24,25]. For example, it is thought to be a crucial factor in the relational difficulties and interpersonal stress characteristic of schizophrenia and antisocial and borderline personality disorders [26][27][28].…”
Section: Introductionmentioning
confidence: 99%